A Study on the Application of Curriculum for Strengthening SWP for Adult Learners - Woo-Hong Cho(조우홍) (한국컴퓨터정보학회논문지, 2021)
The purpose of this study was to apply a teaching method that fits the characteristics of learners through the improvement and application of subjects for reinforcing SWP, and to seek ways to strengthen field practice. As a result of the study, first, as a method of applying learner motivation, it is necessary to conduct discussions by inviting practitioners in the field, and to watch the progress of projects by type of social welfare site. Second, as a way to participate in learners, it is necessary to analyze excellent proposals, participate in events held at welfare sites, present various dilemma cases in the field, and try to overcome ethical dilemmas by sharing cases overcoming dilemma, and to make efforts to list practical skills required in social welfare field practice. Third, it is necessary to apply such methods as phone calls, e-campus, Kakao Talk, Zoom, and counseling techniques that are conducted in the case management process as a way to apply interaction, and discuss issues that are important in the welfare field. KCI Citation Count: 0